Research on noise characteristics and noise control of suspended monorail train - YU Yihang; CHEN Dawei; ZHAO Yanju; SUN Zhaojin; LIU Zongcai (机车电传动)
Compared with conventional rail transit vehicles, suspended monorail trains (sky trains) have great differences in vehicle structure, which contribute to their unique noise characteristics and underscore the value of researching this mode of transportation. In this study, the vibration noise characteristics of sky trains were explored, based on the source-path-receiver mode, and a low-noise scheme was designed to control vehicle noise indexes. Additionally, a simulation and prediction model for vehicle noise was established by utilizing the statistical energy approach (SEA). Furthermore, verification was conducted through noise path experiments, and the results showed a high degree of consistency with the simulations. Sky trains offer significant advantages over conventional rail transit vehicles in terms of noise control, highlighting their ability to better meet noise standards and ensure stable operation.